Steam Reforming of Biogas on Nickel Fiber Mat Catalysts - Quynh Thi Phuong Bui; 김용민; 윤창원; 남석우 (한국에너지학회, 2011)
Nickel fiber mat was investigated as a potential structured catalyst for steam reforming of biogas in the temperature range of 600-700℃. The activity of as-received catalyst was very low owing to the smooth surface of fibers. Pretreatment of the catalyst by oxidation followed by reduction under methane partial oxidation condition significantly improved the catalytic activity, although degradation of the activity was found during the reaction due to oxidation and sintering. This deactivation was retarded by supplying additional hydrogen in the inlet gases or by coating CeO_2 over the catalyst surfaces.